2015
DOI: 10.15616/bsl.2015.21.2.69
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Distribution among Women in Western Shandong Province, East China using Reverse Blot Hybridization Assay

Abstract: Cervical cancer is the third most common cancer in women worldwide and there is a significant association between human papillomavirus (HPV) infection and cervical cancer. Certain HPV groups, labeled high-risk (HR) HPV groups, are strongly associated with malignancies of the human cervix. HPV prevalence and genotype distribution were analyzed using the REBA HPV-ID ® (YD Diagnostics, Yongin, Korea) assay based on the reverse blot hybridization assay (REBA) with a total of 324 liquid-based cytology samples from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…HPV genotypes distribution is various depending on the country, province and substantial geographical variation (Bruni et al, 2010). In previous studies, HPV 16,18,31,33, and 45 were reported to be the most prevalent HPV genotypes associated with cervical cancer in Europe;HPV 16,18,45,31,and 33 were the most common HPV genotypes in North America;and HPV 16,18,45,33,and 31 were the most common in Western and Central Asia,whereas HPV 16,18,58,52, and 33 were the most prevalent HPV genotypes in Eastern Asia (Korea, China, and Japan) Li et al, 2011;Kim et al, 2012;Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…HPV genotypes distribution is various depending on the country, province and substantial geographical variation (Bruni et al, 2010). In previous studies, HPV 16,18,31,33, and 45 were reported to be the most prevalent HPV genotypes associated with cervical cancer in Europe;HPV 16,18,45,31,and 33 were the most common HPV genotypes in North America;and HPV 16,18,45,33,and 31 were the most common in Western and Central Asia,whereas HPV 16,18,58,52, and 33 were the most prevalent HPV genotypes in Eastern Asia (Korea, China, and Japan) Li et al, 2011;Kim et al, 2012;Lee et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Above all, precancerous lesion samples are relatively infrequent compared to normal samples, and there is no idea how much time needed to collect enough samples for statistical analysis. In fact, HSIL samples, which are the most severe precancerous lesion, were collected over three years in Korea and China, but there were about 50 samples [16, 19]. In contrast, microscope slides are sealed with Canada balsam in a vacuum state, so their storage period is longer relatively.…”
Section: Discussionmentioning
confidence: 99%
“…Original Article performed from cervical cytology specimens and used in natural history studies, implementation of screening programs, and follow-up of vaccination studies (Wheeler, 2010;Tay and Tay, 2011;Lee et al, 2015). However, cytology specimens often contain larger numbers of HPV infections, most of which are thought to be transient infections, whereas it is assumed that a lesion is caused by one genotype (Mehlhorn et al, 2013;Ho et al, 1995;Lee, 2013;Lee et al, 2011).…”
Section: Diagnosis Of Hpv Infection Has Beenmentioning
confidence: 99%